Attitudes towards learning English for specific purposes (ESP): A study on changes in attitudes of international studies students at Saigon university - Hoang, Quoc (Edelweiss Applied Science and Technology, 2024)
English for specific purposes (ESP) is absolutely indispensable in any university programs in countries where English is not an official language. After finishing ESP courses, students are expected to approach the best practices that have already been in place around the world. However, students’ attitudes towards ESP are considered as one of the challenges in ESP teaching practice. On this account, this study was conducted to investigate the changes in students’ attitudes towards ESP courses to make some significant suggestions to the future practices in ESP teaching and learning. To achieve this objective, two surveys, called pre-course and post-course ones, were conducted at Saigon University with the participation of 165 students in the pre-course survey and 146 students in the post-course one. They all major in International Studies and have completed an ESP course. The findings show that there are negative and positive changes in students’ attitudes towards the ESP course after they took the ESP course, compared to the result of the survey conducted before the ESP course. The negative changes in students’ attitudes are mainly due to teaching methods and partly due to assessment methods whereas the positive changes in students’ attitudes are partly due to the content of the course. From these findings, the program managers need to make necessary changes to teaching methods to foster students’ motivation, to assessment methods to increase students’ satisfaction, and to the content of the ESP course to improve students’ learning outcomes.